Medical malpractice in hospitals—how healthcare staff feel - Tsai, Shang-Feng; Wu, Chieh-Liang; Ho, Yu-Ying; Lin, Pei-Yi; Yao, Ai-Chu; Yah, Ya-Hui; Hsiao, Chia-Min; You, Yu Huei; Yeh, Te-Feng; Chen, Cheng-Hsu (Frontiers in Public Health, 2023)
Introduction Literature is limited on quantified acute stress reaction, the impact of event scale on medical staff when facing medical malpractice (MMP), and how to individually care for staff. Methods We analyzed data in the Taichung Veterans General Hospital from October 2015 to December 2017, using the Stanford Acute Stress Reaction Questionnaire (SASRQ), the Impact of Event Scale-Revised (IES-R), and the medical malpractice stress syndrome (MMSS). Results and Discussion Of all 98 participants, most (78.8%) were women. Most MMPs (74.5%) did not involve injury to patients, and most staff (85.7%) indicated receiving help from the hospital. The internal-consistency evaluations of the three questionnaires showed good validity and reliability. The highest score of IES-R was the construct of intrusion (30.1); the most severe construct of SASRQ was “Marked symptoms of anxiety or increased arousal,” and the most were having mental and mild physical symptoms for MMES. A higher total IES-R was associated with younger age (<40 y/o), and more severe injury on patients (mortality). Those who indicated receiving very much help from the hospital were those having significantly lower SASRQ sores. Our study highlighted that hospital authorities should regularly follow up on staff’s response to MMP. With timely interventions, vicious cycles of bad feelings can be avoided, especially in young, non-doctor, and non-administrative staff.